English Physicochemical characterization of dehydrated starches extracted from tubers from La Paz - Lopez, Susana Huanca; Vedia, Jorge Fabio Yañiquez; Flores, Valerio Choque; Portugal, Patricia Mollinedo (Food Science and Technology, 2025)
The extraction of starches from four species of tubers, namely potato (Solanum tuberosum), oca (Oxalis tuberosa), papalisa (Ullucus tuberosus), and Isaño (Tropaeolum tuberosum) and their dehydrated products, was carried out to characterize the physicochemical parameters, the microscopy of the starch granules, enzymatic hydrolysis, and gel properties, and to relate the behavior of the starch granule and study its variation with respect to fresh and dehydrated tubers. The results show a difference in the percentage of starch yield depending on the species and its fresh and dehydrated state. A relationship was observed between the content of amylose/amylopectin, morphology of the starch granule, size of the starch granule, and percentage of glucose obtained from the enzymatic hydrolysis process, where starches that have a lower amylose content have smaller, spherical or ellipsoidal granules and are more prone to enzymatic attack. The properties of the gel such as maximum viscosity, breakdown, and setback of the starches obtained were also studied. The sample starches were characterized using X-ray diffraction to identify their crystal structure.